The Effect of Peer Coaching as Health Coaching Support on Parenting Self Efficacy to Infant Care in Early Marriage Mother in The Waipare Public Health Center Working Area - Yosefina Nelista (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2018)
Introduction: Early marriage is a practice that is still common in several countries in the world. Getting married at early age will have an impact on childcare. Marriage at an early age needs to obtain knowledge about childcare. Interventions provided to mothers who marry at early age to change her behavior is health coaching support. The purpose of the study was to analyze the effect of health coaching support by peer coaching method on parenting self-efficacy to infant care in mothers who married at early age. Methods: This study used a quasi-experimental design with one group pre-test and post-test design. The study population was early marriage mothers who had infant. We used purposive sampling technique with a sample of 15 participants. The instrument used in this study was the Maternal Self-Efficacy Scale. Results: The results showed that of the 15 participants, the mean pre-test and mean post-test were 1.73 and 3.46. Wilcoxon test results showed before and after being given health coaching support by peer with p-value 0,000 < α = 0.05, so Ho was rejected and Ha was accepted. This showed that there was a significant influence due to the provision of health coaching support by peer coaching methods on infant care. Conclussions: There was an increase in parenting self-efficacy on infant care in mothers who married at early age. It is expected that parents who married at early age could change their behavior and have confidence in parenting.